Layer Dependence and Light Tuning Surface Potential of 2D MoS2 on Various Substrates. Issue 14 (16th January 2017) - Li, Feng; Qi, Junjie; Xu, Minxuan; Xiao, Jiankun; Xu, Yuliang; Zhang, Xiankun; Liu, Shuo; Zhang, Yue
Abstract : Here surface potential of chemical vapor deposition (CVD) grown 2D MoS2 with various layers is reported, and the effect of adherent substrate and light illumination on surface potential of monolayer MoS2 are investigated. The surface potential of MoS2 on Si/SiO2 substrate decreases from 4.93 to 4.84 eV with the increase in the number of layer from 1 to 4 or more. Especially, the surface potentials of monolayer MoS2 are strongly dependent on its adherent substrate, which are determined to be 4.55, 4.88, 4.93, 5.10, and 5.50 eV on Ag, graphene, Si/SiO2, Au, and Pt substrates, respectively. Light irradiation is introduced to tuning the surface potential of monolayer MoS2, with the increase in light intensity, the surface potential of MoS2 on Si/SiO2 substrate decreases from 4.93 to 4.74 eV, while increases from 5.50 to 5.56 eV on Pt substrate. The I–V curves on vertical of monolayer MoS2 /Pt heterojunction show the decrease in current with the increase of light intensity, and Schottky barrier height at MoS2 /Pt junctions increases from 0.302 to 0.342 eV. The changed surface potential can be explained by trapped charges on surface, photoinduced carriers, charge transfer, and local electric field. Abstract : The surface potential of two dimensional MoS2 is systematically investigated by a KPFM at ambient atmosphere. The surface potential of MoS2 is decreased with the an increase of thickness. The surface potential of monolayer MoS2 is strongly dependent on its adherent substrates. UV irradiation can also modulate the surface potential of the monolayer MoS2 .